Specific and sensitive detection tools for Xanthomonas arboricola pv. corylina, the causal agent of bacterial blight of hazelnut, developed with comparative genomics - Kałużna, Monika; Prokić, Andjelka; Obradović, Aleksa; Weldon, William A.; Stockwell, Virginia O.; Pothier, Joël F. (Frontiers in Plant Science, 2023)
Xanthomonas arboricola pv. corylina (Xac; formerly Xanthomonas campestris pv. corylina) is the causal agent of the bacterial blight of hazelnuts, a devastating disease of trees in plant nurseries and young orchards. Currently, there are no PCR assays to distinguish Xac from all other pathovars of X. arboricola. A comparative genomics approach with publicly available genomes of Xac was used to identify unique sequences, conserved across the genomes of the pathogen. We identified a 2,440 bp genomic region that was unique to Xac and designed identification and detection systems for conventional PCR, qPCR (SYBR® Green and TaqMan™), and loop-mediated isothermal amplification (LAMP). All PCR assays performed on genomic DNA isolated from eight X. arboricola pathovars and closely related bacterial species confirmed the specificity of designed primers. These new multi-platform molecular diagnostic tools may be used by plant clinics and researchers to detect and identify Xac in pure cultures and hazelnut tissues rapidly and accurately.